2020
DOI: 10.1371/journal.pbio.3000361
|View full text |Cite
|
Sign up to set email alerts
|

A wake-active locomotion circuit depolarizes a sleep-active neuron to switch on sleep

Abstract: Sleep-active neurons depolarize during sleep to suppress wakefulness circuits. Wakeactive wake-promoting neurons in turn shut down sleep-active neurons, thus forming a bipartite flip-flop switch. However, how sleep is switched on is unclear because it is not known how wakefulness is translated into sleep-active neuron depolarization when the system is set to sleep. Using optogenetics in Caenorhabditis elegans, we solved the presynaptic circuit for depolarization of the sleep-active RIS neuron during developmen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 100 publications
(202 reference statements)
5
32
0
Order By: Relevance
“…Mechanistic details of RIS activation are beginning to emerge. RIS, like ALA (see below), responds to the epidermal growth factor EGF (Konietzka et al 2020), but is also activated by excitatory input from several other neurons (Maluck et al 2020). These include the forward command interneuron PVC, suggesting a mechanism by which locomotion circuit activity during wake behavior can influence sleep (Maluck et al 2020).…”
Section: Behavioral Quiescence During Developmentally Timed Sleepmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanistic details of RIS activation are beginning to emerge. RIS, like ALA (see below), responds to the epidermal growth factor EGF (Konietzka et al 2020), but is also activated by excitatory input from several other neurons (Maluck et al 2020). These include the forward command interneuron PVC, suggesting a mechanism by which locomotion circuit activity during wake behavior can influence sleep (Maluck et al 2020).…”
Section: Behavioral Quiescence During Developmentally Timed Sleepmentioning
confidence: 99%
“…Activation of the DAF-7 receptor DAF-1 in the tyraminergic RIM neuron and the octopaminergic RIC neuron promotes satiety quiescence (Gallagher et al 2013). How DAF-1 signaling in RIM and RIC promotes behavioral quiescence remains unclear, though it presumably involves RIS activation (Wu et al 2018;Maluck et al 2020).…”
Section: Metabolism Affects Behavioral Statesmentioning
confidence: 99%
“…We compared activity of several neurons during sleep and awake states of unrestrained animals. The RIS interneuron is active at the onset of spontaneous adult sleep, as has been shown during developmentally-timed lethargus sleep ( Turek et al, 2013 ; Maluck et al, 2020 ). The automated closed-loop stimulation system, which requires no user input, further allows unbiased comparison of stimulus-evoked neural responses during alternating sleep and awake bouts within the same animal.…”
Section: Discussionmentioning
confidence: 75%
“…RIS interneuron activity correlates with the onset of developmentally-timed sleep ( Maluck et al, 2020 ; Turek et al, 2013 ) and quiescent behavior in adults ( Steuer Costa et al, 2019 ). To demonstrate neural imaging during spontaneous sleep-wake cycles in the microfluidic device, we recorded activity in the RIS interneuron expressing GCaMP3 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…FLP and PVC neurons synapse onto RIS [57], and, intriguingly, the PVC neurons have recently been shown to be key activators of RIS [58]. Single-cell sequencing showed that NPR-12 is expressed also in RIM neurons [59], which are also involved in RIS activation [58]. However, NPR-12 is not expressed in RIS itself [55].…”
Section: Nlp-29 Acts Through the Neuropeptide Receptor Npr-12mentioning
confidence: 99%